Alih Wahana Film Penyalin Cahaya Karya Wregas Bhanuteja ke dalam Novel Penyalin Cahaya Karya Lucia Priandarini - Paango, Inka Putri; Masie, Sitti Rachmi; Nasiru, La Ode Gusman (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This study aims to describe the adaptation process from the film Penyalin Cahaya by Wregas Bhanuteja to the novel Penyalin Cahaya by Lucia Priandarini. Further, aligned with this research objective, this study is descriptivequalitative research utilizing the concept of adaptation theory by Sapardi Djoko Damono and comparative literature, focusing on the processes of reduction, addition, and variation changes from film to novel. The data were collected through watching, reading, noting, and documentation techniques. The results and discussion of the study showed; (1) The reduction process from film to novel Penyalin Cahaya found 4 data of plot reduction, 1 character reduction, and 6 settings reduction, (2) The addition process included 22 additional plots, 1 additional character, and 5 additional settings, (3) The variation changes found 16 plot changes from film to novel, 1 character change, and 1 setting change. In conclusion, the adaptation from film to novel Penyalin Cahaya was carried out to; (1) Clarify the logic of the story regarding the family life of the main character, Suryani, (2) Clarify the transitions or scene changes in the film that was too fast, (3) Detail the relationships between each scene presented in the film, 4) Emphasize the relationships between characters, and (5) Clarify the conflict atmosphere in the novel.